Analisis Kesalahan Siswa dalam Menyelesaikan Soal Pemecahan Masalah Matematika Berdasarkan Kriteria Newman - Rahmatia Rahmatia; La Eru Ugi; Lisnawati Lisnawati (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2023)
This research is a qualitative research with a quasi-descriptive method. The population in this study were students of class VIII SMP Negeri 33 Buton Tengah, which consisted of 1 class of 24 students. The instruments used in this study were achievement tests and interviews. The research results obtained were the types of errors made by students when solving word problems on a system of two-variable linear equations based on Newman's criteria, for students who made the fewest mistakes including: errors in understanding the problem, transformation errors, and errors in writing answers. For students who are making mistakes include: misunderstanding the problem, transformation errors, process skills errors, and answer writing errors. For students who make the most mistakes include: reading errors, understanding problem errors, transformation errors, process skill errors, and answer writing errors. The causes of reading errors include students not being able to interpret the meaning of each word in the problem correctly. what is known and asked and lack of understanding of the meaning of the question transformation error includes students not writing down the mathematical model of the problem and not being able to make an appropriate mathematical model process skills error includes students who are less skilled in performing calculations and do not carry out the completion process correctly answer writing errors include no make conclusions, do not precisely determine and write down the final results of the settlement.